1997
DOI: 10.1203/00006450-199712000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of Brain and Skeletal Muscle Bioenergetics and Low Brain Magnesium in Juvenile Migraine: An in Vivo 31P Magnetic Resonance Spectroscopy Interictal Study

Abstract: We used phosphorus magnetic resonance spectroscopy (31P MRS) to investigate in vivo the brain and skeletal muscle energy metabolism of 15 children with migraine with aura in interictal periods. Brain 31P MRS disclosed low phosphocreatine and high inorganic phosphate contents, and high intracellular pH in all patients. Calculated [ADP] and the relative rate of mitochondrial oxidation were higher in the brain of patients than in control subjects, whereas the phosphorylation potential was lower. Brain intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 35 publications
2
62
0
Order By: Relevance
“…One study, Boska et al, reported only a depletion of PCr in anterior brain regions of MwA and the occipital cortex of FHM patients (11). The calculated value of the phosphorylation potential was significantly decreased in migraine patients, as reported in a number of studies (8,9,(12)(13)(14)(15) hence has a lower energy reserve, was also frequently observed (8,9,(13)(14)(15)18). The percentage of v/v max was found to be significantly increased in migraine patients (8,9,14,15).…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…One study, Boska et al, reported only a depletion of PCr in anterior brain regions of MwA and the occipital cortex of FHM patients (11). The calculated value of the phosphorylation potential was significantly decreased in migraine patients, as reported in a number of studies (8,9,(12)(13)(14)(15) hence has a lower energy reserve, was also frequently observed (8,9,(13)(14)(15)18). The percentage of v/v max was found to be significantly increased in migraine patients (8,9,14,15).…”
mentioning
confidence: 68%
“…First of all, a significant decrease in [PCr] (8,9,(12)(13)(14)(15)17) and an increase in [P i ] (13-15, 17) resulting in a reduced PCr/P i ratio (5,16,17,19,20) were the most generalized observations, regardless of the brain region. One study, Boska et al, reported only a depletion of PCr in anterior brain regions of MwA and the occipital cortex of FHM patients (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Many previous studies 2 -11 have used 31 P-NMR to examine skeletal muscle energetics during different types of exercise (eg, aerobic and anaerobic) and in different adult populations (eg normal healthy adults, athletes, or patients with heart failure, hyperthyroidism, chronic respiratory impairment, malignant hyperthermia and malnutrition). Fewer studies using exercise protocols with 31 P-NMR have been completed in children and adolescents who are healthy, 12 -14 or diagnosed with migraines 15 or alternating hemiplegia, 16 although sample sizes in prepubertal children have been small (n ¼ 1; 16 n ¼ 2; 15 n ¼ 10 14 ). Children and adolescents have been reported to have a higher pH at the end of exercise 12 -14 and less glycolytic ability 12,14 than adults.…”
Section: Introductionmentioning
confidence: 99%